Review of the Hispaniolan Parachondria (Chondropomorus) complex (Gastropoda: Littorinoidea: Annulariidae) - Watters, G. Thomas (Zootaxa, 2016)
The Parachondria (Chondropomorus) complex in Hispaniola is reviewed. Nineteen species are recognized including eight new species: Parachondria anatolensis n. sp., Parachondria arcisensis n. sp., Parachondria daedalus n. sp., Parachondria heatheraikenae n. sp., Parachondria isabellinus n. sp., Parachondria muchai n. sp., Parachondria silvaticus n. sp., and Parachondria stigmosus n. sp. Distributional and habitat notes are given for additional taxa. Chondropoma marinum “Weinland” Reeve, 1863, is regarded as a nomen dubium. Chondropoma (Chondropomorus) moroni Bartsch, 1946, is reidentified as Crossepoma emilianum (Weinland, 1862). Chondropoma simplex Pfeiffer, 1852, regarded by Bartsch (1946) as a Chondropomorus, is considered a Chondropoma.